Diverse Transcriptional Response of CD4+ T Cells to Stromal Cell-Derived Factor (SDF)-1: Cell Survival Promotion and Priming Effects of SDF-1 on CD4+ T Cells - Yasuhiro Suzuki; Monzur Rahman; Hiroaki Mitsuya (2001)
Abstract Stromal cell-derived factor (SDF)-1 is a ligand for the chemokine receptor CXCR4 which is broadly expressed in lymphocytes, but the effects of SDF-1 on T cells are largely unknown. When examined using complementary DNA microarray, up-regulation of genes which are associated with DNA repair, detoxification, apoptosis, cell morphology, cell adhesion, and signal transduction was seen in CD4+ T cells upon SDF-1 exposure. SDF-1 was shown to promote CD4+ T cell survival through the phosphatidylinositol 3-kinase (PI3K)- and mitogen-activated protein kinase (MAPK)-cascades without cell cycle progression. The proapoptotic Bcl-2 antagonistic of cell death protein was also seen inactivated by the SDF-1-mediated activation of MAPK-extracellular signal-regulated kinases (MEK)-extracellular signal-regulated kinase-ribosomal S6 kinases- and PI3K-pathways. Moreover, the genes known to be associated with cell survival were up-regulated upon SDF-1 exposure and were linked to the MAPK-MEK and PI3K-pathways. Thus, SDF-1 promotes cell survival by two mechanisms: posttranslational inactivation of the cell death machinery and an increased transcription of cell survival-related genes. SDF-1 also primed resting CD4+ T cells for cytokine- and TCR-mediated stimuli. These data suggest that the SDF-1-mediated cell survival combined with its priming function would set T cells to respond to immunologic challenges.